TAMAN PERMAINAN TRADISIONAL DI SPORT CENTER KALIMANTAN SELATAN - Nabila Emiliyana Putri; Bani Noor Muchamad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
South Kalimantan will be involving in national sports events by building a Sports Center as a place for training athletes, so there are opportunities and challenges to reach broader development targets, namely how to create a sports space for the public. Through the concept of Organized Flexible Space, the design of a Traditional Game Park in a Sports Center can become a forum for the development and fostering of recreational sports for the public community through flexible spaces to accommodate various functions (sports, games, and education) based on the context of physical activity of traditional games. The Modular Architecture Approach will ease and accelerate the design process in achieving indoor and outdoor spaces with organized circulation and an attractive and safe arrangement on the contour site.